2005
DOI: 10.1007/s11661-005-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

The microstructural evolution of near beta alloy Ti-10V-2Fe-3Al during subtransus forging

Abstract: The microstructural evolution of titanium alloys during subtransus isothermal forging (IF) has been effectively demonstrated using a testing methodology developed at Imperial College London. Double truncated cone specimen geometries were isothermally deformed at near ␤ transus temperatures to obtain microstructural information for a range of strains within a single specimen. The methodology was applied to the near ␤ alloy, Ti-10V-2Fe-3Al, to determine the effect of strain, strain rate, and IF subtransus temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 5 publications
2
44
0
Order By: Relevance
“…7c). This behavior mirrors typical changes associated with dynamic fragmentation and spheroidization of a lamellae [23]. At the lower temperature (600 1C), the length of a lamellae did not change until e$0.69, but decreased rather rapidly at larger strain almost attaining the value of the lamella length at 800 1C after e¼1.2.…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionsupporting
confidence: 67%
See 3 more Smart Citations
“…7c). This behavior mirrors typical changes associated with dynamic fragmentation and spheroidization of a lamellae [23]. At the lower temperature (600 1C), the length of a lamellae did not change until e$0.69, but decreased rather rapidly at larger strain almost attaining the value of the lamella length at 800 1C after e¼1.2.…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionsupporting
confidence: 67%
“…Such a relationship may be expected to be weak especially since the bulk of the imposed deformation was accommodated by the bcc b phase, which tends to exhibit limited plastic anisotropy compared to the hcp a phase in titanium alloys. Hence, as noted above, it is likely that the observed flow softening may be ascribed primarily to slip transfer [10] and fragmentation of the b matrix [23]. The latter effect would reduce the constraint imposed on the deformation of b and hence the stress required to bring about its deformation.…”
Section: Flow Behavior and Kinetics Of Microstructure Evolutionmentioning
confidence: 89%
See 2 more Smart Citations
“…[11][12][13] As a result, several deformation mechanisms have been proposed to explain the behavior of Ti-6-4 and therefore facilitate more accurate process modeling. Unfortunately, the larger a phase volume fraction (50 pct in Ti-6-4 compared to 13 pct in Ti-10-2-3) present in a + b alloys at typical industrial processing temperatures has been shown to affect the deformation mechanisms, preventing the simple adoption of mechanisms from one alloy type to another.…”
Section: Introductionmentioning
confidence: 99%